Digital fluency and the use of virtual environments: the characterization of nursing students - Costa, Priscila Berenice; Prado, Cláudia; Oliveira, Luciana de Fátima Teixeira de; Peres, Heloísa Helena Ciqueto; Massarollo, Maria Cristina Komatsu Braga; Fernandes, Maria de Fátima Prado; Leite, Maria Madalena Januário; Freitas, Genival Fernandes de (Revista da Escola de Enfermagem da USP, 2011)
The objective of this study was to characterize the profile of nursing undergraduate students, identify their digital fluency, knowledge, ability and interest in using virtual learning environments. This quantitative, exploratory-descriptive study, was performed with 51 nursing undergraduate students. Data collection was performed using a questionnaire. All 51 subjects (100%) reported having some knowledge in informatics, 26 (49%) of which reported having an intermediate knowledge; 47 (92%) use the Internet everyday; 51 (100%) surf the social networks and have e-mail; 51 (100%) are MSN users; 32 (62.7%) use Skype; 41 (82%) use Chat applications; 33 (64.7%) use discussion forums; 22 (43%) use blogs; 33 (64.7%) frequently use Moodle and 26 (51%) use COL; 45 (88.2 %) reported interest in using virtual learning environments. The students are digitally fluent and show knowledge, ability and significant interest regarding the use of virtual learning environments in their academic studies.